2009
DOI: 10.1016/j.apradiso.2008.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Studies into radiolytic decomposition of fluorine-18 labeled radiopharmaceuticals for positron emission tomography

Abstract: Radiolytic decomposition of high specific concentration radiopharmaceuticals is an undesired side-effect that can hamper development of novel PET tracers. This was particularly evident in a series of carbon-11 and fluorine-18 labeled mono- and dimethyl-substituted aryl amines, where rapid decomposition was observed in isolation and formulation steps. We tested a number of additives that inhibit radiolysis and can be safely added to the synthesis procedures (purification and isolation) and reformulation steps t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 34 publications
0
54
0
Order By: Relevance
“…The addition of ascorbic acid as an antioxidant stabilizer to the reaction mixture before the HPLC purification also effectively prevented the radiolysis. [19] Consequently, we found that the six kinds of 2-aryl- 11 C]2 in class C were very unstable, and they required not only ascorbic acid but also synthetic conditions with the lower radioactivity (~15 GBq). The reaction with higher radioactivity (> 15 GBq) gave many kinds of products among which it was too difficult to isolate the desired labeled compound.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of ascorbic acid as an antioxidant stabilizer to the reaction mixture before the HPLC purification also effectively prevented the radiolysis. [19] Consequently, we found that the six kinds of 2-aryl- 11 C]2 in class C were very unstable, and they required not only ascorbic acid but also synthetic conditions with the lower radioactivity (~15 GBq). The reaction with higher radioactivity (> 15 GBq) gave many kinds of products among which it was too difficult to isolate the desired labeled compound.…”
Section: Resultsmentioning
confidence: 99%
“…Since numerous publications describe the synthesis of [ 18 F]FBA in RCY ranging from 50 to 72 % [20, 21], we investigated the reason for the low formation of [ 18 F]FBA in our hands. We considered radiolysis of [ 18 F]FBA during SPE purification in the presence of water as a possible reason for low yields from high starting activities [22]. This possibility was explored by synthesizing [ 18 F]FBA with escalating amounts of radioactivity and a negative correlation between starting activities and synthesis yield was indeed observed (Suppl.…”
Section: Discussionmentioning
confidence: 99%
“…66 Ethanol and ascorbate are among the most effective radioprotectants. Fortuitously, reformulation of products often requires the use of ethanol, which remains in the final product as both a cosolvent and radioprotectant.…”
Section: Factors Associated With Preparation Proceduresmentioning
confidence: 99%